Optimal Capital Adequacy Ratio in an Islamic Banking System - Habib Ansari Samani; Mahmoud Eisavi; Hasan Amoozad Khalili (International Journal of Business and Development Studies, 2021)
With the advent and growth of Islamic banking, various researches have been performed to analyze the performance and mechanisms of regulatory rules of this industry. Due to the special role of banks in the economic systems of countries and the world, significant regulatory and control rules were used. In the meantime, the commitment to implement the rules of the Basel II Capital Accord as the most important international agreement to ensure banking health is of particular importance, and among all the issues raised in this agreement, compliance with the minimum capital adequacy has been considered by many researches. One of the most important questions in this area is whether the Basel method of calculation and the minimum rate (8%) is appropriate for the Islamic banking system? To answer this question, this study has calculated the capital adequacy ratio for Islamic banks of Iran and by modeling its effect on the bank’ profit efficiency, as the most important incentive indicator for banks, has estimated an optimal rate these banks.